Tinjauan Yuridis Terhadap Pertanggungjawaban Pidana Bagi Seorang Psikopat Dalam Tindak Pidana Pembunuhan - Yudhiati, Ega Septianing; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Crime in the community is currently in a state of fret. of the many types of crimes, murder which lately often occur. a lot of things behind someone commit robbery to murder them a sense revenge .from some homicides that occurred, can not be said again as an ordinary murder because not only kill the perpetrators also take action in the author's view is too cruel, that mutilated the victim's body and even in some cases the author analyzes motive for murder just because of jealousy. There are killers who have a symptom that indicates that someone is experiencing imbalances or failure in aligning urges constructive and destructive in itself, often called a psychopath. Psychopaths also no mention of a madman without mental disorders.In accordance with the above description, the writer interested to do research under the title Against Judicial Review of Criminal Liability For A Psychopath In Crime Murder. Then to find out how the criminal liability and punishment on the perpetrators of the crime of murder committed by a psychopath. The last to know the limits of the law a person can be said to be a psychopath.Results of the discussion in this paper is, first, that the criminal liability and punishment on the perpetrators of criminal acts committed murder psychopaths can account for his actions before the law under Article 338 of the Criminal Code. Then the perpetrators of the murder by category psychopaths can not be categorized as a lunatic or a disability of his soul, because he still has the power of thought in a healthy and stable, so it can be sentenced to criminal seseuai with the rules of the Code of Criminal prevailing in Indonesia at this time.Keywords: Accountability, killing, psychopathic